CAPABILITIES OF APPLYING VISIBLE LIGHT RAYS IN THE SYSTEMS OF HIDDEN INFORMATION TRANSMITTING - I. V. Pyslar; V. V. Brailovsky; M. G. Rozhdestvenska; M. M. Ivanchuk (Системный анализ и прикладная информатика)
Security In the paper some aspects of visible light pulses using for hidden information transmitting are considered. We have investigated perception of the human vision to visual light pulses which have different power and frequency. It is established that pulsed light source becomes invisible at certain ratio of radiating light stream and ambient light level (background lighting (BL)). For example, in the case of background lighting E = 400 lx light pulses following with frequency 50 Hz are invisible when their power is less than 0.12 W. In the paper we represented experimental frequency dependence of the power of light pulses which are invisible for human eye at BL preset level.To eliminate the influence of distracting and masking factors (for example, BL pulsations) we offer to choose LED matrixes powered by stabilized adjustable DC power supply unit as an optimal BL source. Based on experimental data about current and temperature dependences of light stream power and LED matrix radiation spectra we developed a method of assignment of BL level by changing LED current. Approximating equation for dependence of light stream quantity versus LED current in the case of thermostatting is obtained. Temperature self-regulation effect of the heater, which has positive temperature coefficient of resistance, can satisfactorily solve the problem of temperature stabilization of LED background lighting source. In the case of thermostat heater made from material with positive temperature coefficient of resistance 0.48 K-1 the change of LED matrix temperature was 7 times less than without thermostat.To provide research in wide frequency and duration ranges of pulse sequences (10–3–103 Hz and 10–7–1 s) a pulse generator was developed and made using microcontroller PIC18F2550.